Studies on morphology of polyaniline films formed at liquid-liquid and solid-liquid interfaces at 25 and 5 A degrees C, respectively, and effect of doping - Waghmode, Babasaheb J.; Patil, Sagar H.; Jahagirdar, Mandar M.; Patil, Virendra S.; Waichal, Rupali P.; Malkhede, Dipalee D.; Sathaye, Shivaram D.; Patil, Kashinath R. (Colloid and Polymer Science, 2014)
It is well accepted that the morphology of the nanomaterials has great effect on the properties and hence their applications. Therefore, morphology of materials has become a focus of research in the scientific world. The present study shows that interfacial polymerization and subsequent self-assembly provides a control over the morphology, nanorod/nanosheet, of polyaniline (PANI) films synthesized by liquid-liquid interface reaction technique and solid-liquid interface reaction technique. The synthesized PANI films and its particulate structure are characterized by using various spectroscopic techniques such as UV-visible, ATR-IR, Raman and XPS. The study confirmed the formation, the structure, the size and shape of particles and morphology of PANI by using analytical techniques namely, SAED, SEM and TEM. An important observation is that doping with HCl significantly improves the nanorod formation at the interface. The doped PANI electrode exhibits a higher area with rectangular shape in CV cycle and better cycle stability when compared with the performance of undoped PANI films. We believe that the results of these studies can give valuable leads to manoeuvre formation of PANI films with desired morphology for various applications.
Keywords: interfacial polymerization; Liquid-liquid interface; Nanorods; nanosheets; polyaniline; Self-assembly; Solid-liquid interface; Thin films

To form layer by layer composite film in view of its application as supercapacitor electrode by exploiting the techniques of thin films formation just around the corner - Patil, Sagar H.; Gaikwad, Aarti P.; Sathaye, Shivaram D.; Patil, Kashinath R. (Electrochimica Acta, 2018)
A method is described to form robust composite supercapacitor electrodes consisting of polyaniline (PANI)-graphene (GNS) and PANI-MoS2 nanosheets wherein composites are formed by Layer by Layer (LbL) deposition. PANI layer consisting of 10-15 nm particle size was formed by LLIRT, while GNS and MoS2 layers were formed by modified LLIRT. A special feature of the development is the architecture which is rarely found in the literature wherein singular components are stacked over each other to form a composite. The architecture is found to show strong synergistic effects suitable for high performance supercapacitor applications. The composites were characterized by using X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), high resolution transmission electron microscopy (HRTEM) etc. The characterization indicates the formation of composites having uniform distribution of PANI nanoparticles over the 2D nanosheets of GNS and MoS2 respectively. The electrochemical performance of the composites was evaluated by cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and Galvanostatic Charge Discharge (GCD). The composite layer consisting of PANI-GNS alternate layers, showed an excellent specific capacitance (C-sp) of 549 Fg(-1) while PANI-MoS2 alternate layers and PANI layers showed C-sp to be (413 F g(-1)) and (185 F g(-1)) respectively. It is proposed that C-sp stability of the composites is greatly enhanced by the architecture of composite formation through LbL deposition approach. PANI-GNS showed high stability (95% retention of C-sp), PANI-MoS2 (94% retention of C-sp) as against single component capacitance of PANI (67% retention of C-sp). The results reveal the importance of the architecture of composite formation. The architecture of depositing alternate layers of components to form a composite would have special properties leading to synergistic effect in the applications. The present communication is a proof of this concept. It shows the boost in the charge storage resulting in stable robust supercapacitors formation. We predict similar advantages in other applications such as solar energy conversion, sensors, catalysis, etc. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: GNS; Layer-by-Layer deposition; MoS2 nanosheets; polyaniline; Supercapacitors